The Feasibility of a Five-Year Educational Requirement for New York CPAs (Book). - Keller, Thomas F.; Langenderfer, Harold Q. (The Accounting Review, 1972)
Reviews the book "The Feasibility of a Five-Year Educational Requirement for New York CPAs," edited by Stephen Feldman and Joel Kauffman.